2023
DOI: 10.1101/2023.02.14.528476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sarbecoviruses of British Horseshoe Bats; Sequence Variation and Epidemiology

Abstract: Horseshoe bats are the natural hosts of the Sarbecovirus subgenus that includes SARS-CoV-1 and 2. Despite the devastating impacts of the COVID-19 pandemic, there is still little known about the underlying epidemiology and virology of sarbecoviruses in their original hosts, leaving large gaps in our pandemic preparedness. Here we describe the results of PCR testing for sarbecoviruses in the two horseshoe bat species (Rhinolophus hipposideros and R. ferrumequinum) present in Great Britain, collected in 2021-22 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Thus far, no infection with SARS-CoV-2 has been reported in horseshoe bats (Rhinolophus spp.) in Britain or mainland Europe [28][29][30] although other related coronaviruses have been detected in these species. Reports in European deer prior to 2022 all failed to detect any exposure [31][32][33], but 57 % of fallow deer in Dublin, Ireland, seroconverted in early 2022 [34] and sporadic seropositivity in fallow and red deer in Spain in 2021-22 has also been reported [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, no infection with SARS-CoV-2 has been reported in horseshoe bats (Rhinolophus spp.) in Britain or mainland Europe [28][29][30] although other related coronaviruses have been detected in these species. Reports in European deer prior to 2022 all failed to detect any exposure [31][32][33], but 57 % of fallow deer in Dublin, Ireland, seroconverted in early 2022 [34] and sporadic seropositivity in fallow and red deer in Spain in 2021-22 has also been reported [35].…”
Section: Introductionmentioning
confidence: 99%
“…The present study focused on species of wild animals present in Great Britain that were assessed to be of higher risk for SARS-CoV-2 spillover in 2021, when the study was begun. These included horseshoe bats (the subject of a separate report [28]), mustelids, small carnivores and cricetid rodents.…”
Section: Introductionmentioning
confidence: 99%
“…A completely negative finding in the two horseshoe bat species was unexpected, particularly as these species are the natural hosts of SARS-like viruses and the PCR assays used in this study should have detected known horseshoe bat sarbecoviruses. Our similar study of UK horseshoe bats did however demonstrate that presence or absence of sarbecoviruses can be very species specific with lesser horseshoe bats having a 44 % positivity rate on faecal or rectal swab samples but no detection at all in greater horseshoe bats [42]. Studies in SE Asia present with very different results with high positivity rates and sarbecoviruses detected in multiple species [43].…”
Section: Discussionmentioning
confidence: 52%
“…Thus far, no infection with SARS-CoV-2 has been reported in Horseshoe bats (Rhinopholus spp) in Britain or mainland Europe (Orłowska, Smreczak et al 2022, Sander, Moreira-Soto et al 2022, Apaa, Withers et al 2023 although other related coronaviruses have been detected in these species. Reports in European deer prior to 2022 all failed to detect any exposure (Holding, Otter et al 2022, Moreira-Soto, Walzer et al 2022, Wernike, Fischer et al 2022 , however 57% of fallow deer in Dublin seroconverted in early 2022 (Purves, Brown et al 2023) and sporadic seropositivity in fallow and red deer in Spain in 2021-22 has also been reported (Encinas, Escalera et al 2023)Wild animal surveillance studies in mainland Europe have indicated sporadic detection in wild mustelids, including by qPCR in wild American mink (N.vison), particularly near farmed mink outbreaks, and one otter (L. lutra) (Aguiló-Gisbert, Padilla-Blanco et al 2021, Padilla-Blanco, Aguiló-Gisbert et al 2022, Sikkema, Begeman et al 2022.…”
Section: Introductionmentioning
confidence: 98%
“…This study focused on species of wild animals present in Great Britain that were assessed to be of higher risk for SARS-CoV-2 spillover in 2021, when the study was begun. These included, horseshoe bats (subject of a separate report ( (Apaa, Withers et al 2023)) mustelids, small carnivores and cricetid rodents.…”
Section: Introductionmentioning
confidence: 99%